2018
DOI: 10.1128/jvi.01251-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Persistence of Chimeric Virus after Substitution of the Kaposi's Sarcoma-Associated Herpesvirus LANA DNA Binding Domain with That of Murid Herpesvirus 4

Abstract: KSHV is a human oncogenic virus for which there is no tractable, immunocompetent animal model of infection. MuHV-4, a related rodent gammaherpesvirus, enables pathogenesis studies in mice. In latency, both viruses persist as extrachromosomal, circular genomes (episomes). LANA proteins encoded by KSHV (kLANA) and MuHV-4 (mLANA) contain a C-terminal DNA binding domain (DBD) that acts on the virus terminal repeats to enable episome persistence. mLANA is a smaller protein than kLANA. Their DBDs are structurally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…LANA expression levels from infected BHK-21 cells were quantified by extracting cDNA (5 PFU/cell for 8 h) as described previously ( 34 ). Real-time qPCR was performed with the DyNAmo SYBR FlashGreen qPCR kit (Thermo Fisher Scientific), using primers specific for DNA encoding the C-terminal region of kLANA, (kLANA RT2-F: 5′-TGG​TTG​TTG​GTA​TCT​TGG-3′ and kLANA RT2-R: 5′-CCT​GGA​GTT​CGT​ATG​AGG-3′), and previously described primers for MHV68 M3 and for glyceraldehyde-3-phosphate dehydrogenase ( 34 ). ΔΔCT values (where CT is the threshold cycle) were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LANA expression levels from infected BHK-21 cells were quantified by extracting cDNA (5 PFU/cell for 8 h) as described previously ( 34 ). Real-time qPCR was performed with the DyNAmo SYBR FlashGreen qPCR kit (Thermo Fisher Scientific), using primers specific for DNA encoding the C-terminal region of kLANA, (kLANA RT2-F: 5′-TGG​TTG​TTG​GTA​TCT​TGG-3′ and kLANA RT2-R: 5′-CCT​GGA​GTT​CGT​ATG​AGG-3′), and previously described primers for MHV68 M3 and for glyceraldehyde-3-phosphate dehydrogenase ( 34 ). ΔΔCT values (where CT is the threshold cycle) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Female C57 BL6 J mice (age 6 to 8 wk) were infected intranasally with 10 4 PFU in 20 μL of PBS under isofluorane anesthesia. Single-cell suspensions of spleens were prepared as described previously ( 34 ). For the infectious center assay (ex vivo reactivation assay), serially diluted splenocyte suspensions from individual mice were cocultured with 5 × 10 5 BHK-21 cells in 6-cm dishes for 5 d at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, biology common between the mouse and human GHV can illuminate conserved evolutionary strategies that are likely further refined by the human GHV. Approaches to test how factors encoded by the human GHV influence the infected B cells include gain of function experiments that introduce human GHV genes into MHV68 or genetically complement MHV68 mutants [ 145 , 146 , 147 , 148 , 149 ]. The analysis of EBV and KSHV in humanized mice is an exciting advancement that enables some degree of B cell interactions with cognate T cells [ 141 , 150 , 151 ].…”
Section: Germinal Center Processes That Shape B Cell Evolution Andmentioning
confidence: 99%
“…mLANA is a functional homolog of KSHV LANA that promotes episomal maintenance of the genome in vivo [ 148 , 149 ]. mLANA also impairs p53-induction of cell death during lytic infection [ 179 , 180 ].…”
Section: Germinal Center Processes That Shape B Cell Evolution Andmentioning
confidence: 99%
“…This study was the first to tackle the immune evasion mechanisms of GMPs in vivo . Interestingly, three recent studies used chimeric MuHV-4 recombinant viruses where mLANA was replaced by functional KSHV LANA-1 (Gupta et al, 2017; Habison et al, 2017; Pires de Miranda et al, 2018). These studies demonstrated the ability of LANA-1-expressing chimeric MuHV-4 to be maintained and establish latency in vivo , although at lower levels compared to wildtype MuHV-4.…”
Section: Genus Rhadinovirusmentioning
confidence: 99%